Novel toolkit of gastronomic systems research (GSR) for unraveling drivers of food choice for India - CGIAR Research Program on Rice (2021)
The toolkit is a proof of concept that can help policy makers and nutritionists develop more targeted nutrition interventions, which can aid in the development of planetary health diets in various contexts around the world. We piloted the toolkit in eastern India.